Hierarchical double-layer microneedles accomplish multicenter skin regeneration in diabetic full-thickness wounds - Xiaoqi Huang; Xingtang Niu; Yuan Ma; Xinhui Wang; Ting Su; Yu He; Feng Lu; Jianhua Gao; Qiang Chang (Journal of Advanced Research)
Introduction: Managing large chronic wounds presents significant challenges because of inadequate donor sites, infection, and lack of structural support from dermal substitutes. Hydrogels are extensively used in various forms to promote chronic wound healing and provide a three-dimensional spatial structure, through growth factors or cell transport. Objectives: We present a novel multicenter regenerative model that is capable of regenerating and merging simultaneously to form a complete layer of skin. This method significantly reduces wound healing time compared to the traditional centripetal healing model. We believe that our model can improve clinical outcomes and pave the way for further research into regenerative medicine. Methods: We prepared a novel multi-island double-layer microneedle (MDMN) using gelatin-methacryloylchitosan (GelMA-CS). The MDMN was loaded with keratinocytes (KCs) and dermal fibroblasts (FBs). Our aim in this study was to explore the therapeutic potential of MDMN in a total skin excision model. Results: The MDMN model replicated the layered structure of full-thickness skin and facilitated tissue regeneration and healing via dual omni-bearing. Multi-island regeneration centres accomplished horizontal multicentric regeneration, while epidermal and dermal cells migrated synchronously from each location. This produced a healing area approximately 4.7 times greater than that of the conventional scratch tests. The MDMN model exhibited excellent antibacterial properties, attributed to the chitosan layer. During wound healing in diabetic mice, the MDMN achieved earlier epidermal coverage and faster wound healing through multi-island regeneration centres and the omnidirectional regeneration mode. The MDMN group displayed an accelerated wound healing rate upon arrival at the destination (0.96 % ± 0.58 % vs. 4.61 % ± 0.32 %). Additionally, the MDMN group exhibited superior vascularization and orderly collagen deposition. Conclusion: The present study presents a novel skin regeneration model using microneedles as carriers of autologous keratinocytes and dermal fibroblasts, which allows for omni-directional, multi-center, and full-thickness skin regeneration.